2015
DOI: 10.1080/19491034.2015.1126028
|View full text |Cite
|
Sign up to set email alerts
|

Marker gene tethering by nucleoporins affects gene expression in plants

Abstract: In non-plant systems, chromatin association with the nuclear periphery affects gene expression, where interactions with nuclear envelope proteins can repress and interactions with nucleoporins can enhance transcription. In plants, both hetero- and euchromatin can localize at the nuclear periphery, but the effect of proximity to the nuclear periphery on gene expression remains largely unknown. This study explores the putative function of Seh1 and Nup50a nucleoporins on gene expression by using the Lac Operator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…It is worth mentioning that several light-induced genes such as CHLOROPHYLL A/B-BINDING ( CAB ), RUBISCO SMALL SUBUNIT ( RBCS ), PLASTOCYANIN ( PC ) and GENOMES UNCOUPLED 5 ( GUN5 ) have been observed to re-position to the nuclear periphery in response to light [ 35 •• ]. Tethering experiments of reporter genes to a plant nucleoporin showed an increase in gene expression [ 36 ], whereas NUP1-associated sequences were enriched in repressed genes [ 31 ].…”
Section: Novel Discoveries Light Up Plant Nuclear Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that several light-induced genes such as CHLOROPHYLL A/B-BINDING ( CAB ), RUBISCO SMALL SUBUNIT ( RBCS ), PLASTOCYANIN ( PC ) and GENOMES UNCOUPLED 5 ( GUN5 ) have been observed to re-position to the nuclear periphery in response to light [ 35 •• ]. Tethering experiments of reporter genes to a plant nucleoporin showed an increase in gene expression [ 36 ], whereas NUP1-associated sequences were enriched in repressed genes [ 31 ].…”
Section: Novel Discoveries Light Up Plant Nuclear Architecturementioning
confidence: 99%
“…These studies indicate that the plant NE potentially holds a dual role in regulating gene expression depending on the chromatin context and precise topology on the nuclear periphery (NPC versus lamin-like protein association) [ 31 , 35 •• , 36 ]. Although yeast and mammalian systems have provided key examples demonstrating a direct association between gene repositioning to the nuclear periphery with gene activation or repression, there is very limited information correlating nuclear positioning and gene expression in plants [ 14 , 35 •• ].…”
Section: Novel Discoveries Light Up Plant Nuclear Architecturementioning
confidence: 99%
“…In Drosophila melanogaster, chromatin mobility is important for interacting with distinct nuclear compartments during differentiation (Thakar and Csink, 2005). Furthermore, altering nuclear morphology changes chromatin organization and disrupts genome function (Lanctôt et al, 2007;Ramdas and Shivashankar, 2015;Smith et al, 2015).…”
Section: Dynamic Organization Of the Nucleoplasm General Nuclear Orgamentioning
confidence: 99%
“…Feng et al (2014) visualized lightmediated chlorophyll a/b-binding protein (CAB) loci repositioning from the nuclear interior to the periphery, which was associated with increased CAB gene expression. Smith et al (2015) showed that artificially tethering a locus to a nucleoporin enhances its expression. Another group performed an in vivo study that identified and characterized Arabidopsis chromatin regions that preferentially associated with the nuclear periphery.…”
Section: Dynamic Organization Of the Nucleoplasm General Nuclear Orgamentioning
confidence: 99%
“…The chromatin tagging system revealed that the arrangement of chromatin positioning was closely related to the regulation of gene activity. For example, the nuclear lamina regulates the transcriptional activity through repositioning of specific chromatins in animal cultured cells and A. thaliana (Reddy et al 2008, Kumaran and Spector 2008, Finlan et al 2008, Smith et al 2015. The chromatin tagging system also contributes to the analyses of the high-order chromatin structure.…”
mentioning
confidence: 99%